Calcifications in Thyroid Tumors on Ultrasonography: Calcification Types and Relationship with Histopathological Type - Kobayashi, Kaoru; Fujimoto, Tomoko; Ota, Hisashi; Hirokawa, Mitsuyoshi; Yabuta, Tomonori; Masuoka, Hiroo; Fukushima, Mitsuhiro; Higashiyama, Takuya; Kihara, Minoru; Ito, Yasuhiro; Miya, Akihiro; Miyauchi, Akira (Ultrasound International Open, 2018)
The purpose of the study is to clarify the prevalence of calcifications within thyroid tumors on ultrasonography as well as the relationship between the calcification and histopathological types. Calcifications were classified into 6 (or 8) types according to their shape, size, and region. The prevalence of calcifications and types were investigated in new outpatients and patients who underwent thyroid surgery.Among 2,902 nodules in 2,678 new outpatients, 747 nodules (26%) had calcifications. The types showed a wide distribution. Among 941 patients with papillary carcinoma (PC), 725 patients (77%) had calcifications, and the types showed a wide distribution. 18 patients with the diffuse sclerosing variant of PC only showed punctate microcalcifications in the parenchyma (100%), 32 patients with the cyst-forming type of PC mostly fragmentary and massive types (100%), and 161 metastatic lymph nodes from PC mostly punctate microcalcifications and fragmentary types (48%). Among 337 patients with follicular carcinoma, 79 patients (23%) had calcifications, and the types were mostly fragmentary, massive, and egg-shell types. Among 41 patients with undifferentiated carcinoma, 33 patients (80%) presented with calcifications, which were mostly the massive and egg-shell types. Among 137 patients with medullary carcinoma, 99 patients (72%) had calcification, and the types showed a wide distribution. None of 173 patients with primary thyroid lymphoma had calcifications (0%).Calcifications on ultrasonography can be one of the characteristic findings and a full understanding of the prevalence of calcifications and types will markedly contribute to the ultrasonic diagnosis of thyroid tumors.
Keywords: thyroid; tumor; ultrasound; histopahology; calcifications